Famille ecclésiale de vie consacrée: Une nouvelle forme d'institut de vie consacrée - Balog, Márta (Studia canonica, 2017)
Most new associations founded after the Second Vatican Council with the characteristics of a new form of evangelical life, after the publication of the 1983 Code of Canon Law, pretended to be recognized as new forms of consecrated life based on canon 605. In these plurivocational foundations are found common ecclesial and spiritual elements, and the desire on the part of the founders or founding generations to preserve unity within their community. Their complexity, however, has developed two tracks of recognition: (1) a form of institution with the visum of the Congregation for Institutes of Consecrated life and Societies of Apostolic life, and (2) a new associative forms with the Pontifical Council for the Laity.